Cross-cultural adaptation and psychometric properties of the Thai version of the patient-reported outcomes measurement information system short form- depression 8a in individuals with chronic low back pain - Ruetaichanok Sansatan; Rotsalai Kanlayanaphotporn; Mark P. Jensen; Helena Correia; Prawit Janwantanakul (SpringerOpen, 2024)
Abstract Background The study aimed to cross-culturally adapt the Patient-Reported Outcomes Measurement Information System Short Form v1.0 - Depression 8a (PROMIS SF v1.0 - Depression 8a) into Thai and evaluate its psychometric properties in individuals with chronic low back pain (CLBP). Methods The PROMIS SF v1.0- Depression 8a was translated and cross-culturally adapted into Thai using the Functional Assessment of Chronic Illness Therapy translation methodology. Two hundred and sixty-nine individuals with CLBP completed the Thai version of PROMIS SF v1.0- Depression 8a (T-PROMIS-D-8a) scale and a set of measures assessing validity criterion domains. Structural validity, internal consistency, and test-retest reliability at a 7-day interval of the T-PROMIS-D-8a scale were computed and its construct validity was evaluated by computing correlations with the Thai version of Patient Health Questionnaire-9 (T-PHQ-9), Numeric Rating Scale of pain intensity (T-NRS), and Fear Avoidance Beliefs Questionnaire (T-FABQ). Results Data from 269 participants were analyzed. Most participants were women (70%), and the sample had a mean age of 42.5 (SD 16.6) years. The findings supported the unidimensionality, internal consistency (Cronbach's alpha = 0.94), and test-retest reliability (ICC [2,1] = 0.86) of the T-PROMIS-D-8a. A floor effect was observed for 16% of the sample. Associations with the T-PHQ-9, T-NRS, and T-FABQ supported the construct validity of the T-PROMIS-D-8a. Conclusions The T-PROMIS-D-8a was successfully translated and culturally adapted. The findings indicated that the scale is reliable and valid for assessing depression in Thai individuals with CLBP.